1919 Pa. Laws 710, No. 286, § 1 - (:unkn) unknown (General Publisher, 1919)
The department may adopt and enforce rules and regulations governing the having, using, storage, sale and keeping of gasoline, naptha, kerosene, or other substance of like character, blasting powder, gun powder, dynamite, or any other inflammable or combustible chemical products or substances or materials. The department may also adopt and enforce rules and regulations requiring the placing of fire extinguishers in buildings.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER